2015
DOI: 10.3389/fpsyg.2015.00851
|View full text |Cite
|
Sign up to set email alerts
|

The adaptive value associated with expressing and perceiving angry-male and happy-female faces

Abstract: Facial expressions are valuable for conveying and understanding the inner thoughts and feelings of the expressor. However, the adaptive value associated with a specific expression on a male face is different from a female face. The present review uses a functional-evolutionary analysis to elucidate the evolutionary advantage in the expression and perception of angry-male and happy-female faces over angry-female and happy-male faces. For the expressors, it is more advantageous for men to show angry facial expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 77 publications
3
19
0
Order By: Relevance
“…The gender results presented in this experiment go hand in hand with previous results of higher accuracy for happy than for angry female faces and for angry than for happy male faces, but only in the context of a gender categorization task (see Becker et al 2011;Hess et al, 2009;Pérez-Moreno et al, 2016). This result can be explained by the fact that angry females might be misidentified as males and happy males as females as has been reported previously in our laboratory (see Aguado, García-Gutiérrez, & Serrano-Pedraza, 2009;Grossman & Wood, 1993;Plant, Hyde, Keltner, & Devine, 2000;Tay, 2015).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The gender results presented in this experiment go hand in hand with previous results of higher accuracy for happy than for angry female faces and for angry than for happy male faces, but only in the context of a gender categorization task (see Becker et al 2011;Hess et al, 2009;Pérez-Moreno et al, 2016). This result can be explained by the fact that angry females might be misidentified as males and happy males as females as has been reported previously in our laboratory (see Aguado, García-Gutiérrez, & Serrano-Pedraza, 2009;Grossman & Wood, 1993;Plant, Hyde, Keltner, & Devine, 2000;Tay, 2015).…”
Section: Resultssupporting
confidence: 73%
“…Furthermore, the brief exposure times would have impeded more detailed visual inspection and analysis of other genderrelevant features that might counteract the influence of the salient expression features. According to this account, gender misidentifications should have been more likely in the cases of angry female and happy male faces (Aguado et al, 2009;Grossman & Wood, 1993;Tay, 2015). In fact, the accuracy of gender discrimination in Experiment 2 for the different combinations of gender and expression confirms this prediction is a better discrimination of gender for happy male than for angry female faces.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, the finding that young adults more quickly detected male fearful faces is worth noting in and of itself. The tendency towards faster detection of male expressive faces over female faces among adults has been shown in previous studies (Tay, ; Williams & Mattingley, ). This bias in attention allocation could be explained by a different cognitive mechanism whereby male faces are perceived as more threatening than female ones (Harris, Hayes‐Skelton, & Ciaramitaro, ).…”
Section: Discussionsupporting
confidence: 75%
“…35 The findings of this study suggest a different effect of dental appearance on self-reported discrimination according to sex. Studies have reported that females smile more than males in social situations 36 and when social tension is high. [37][38][39] The fact is that, in social interactions, one's attention is mainly directed towards the mouth and eyes of the speaker's face.…”
mentioning
confidence: 99%